Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ø§Ù„Ø°ÙƒØ§Ø¡ Ø§Ù„Ù…Ø¹Ø±ÙÙŠ ÙˆÙ†ØªØ§Ø¦Ø¬ Ø¯Ø±Ø³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø«Ø§Ù†ÙŠØ© - Nasrullah, Muhammad; Sholihah, Siti (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2019)
This study aimed to reveal the correlation between cognitive intelligence and Arabic language learning outcomes in 10th grade students of MIA MAN 2 Madiun. This research uses a quantitative approach. The findings of this study are: 1) cognitive intelligence of 10th grade students of MIA MAN 2 Madiun at the moderate level with a percentage of 70.66%. 2) the results of learning Arabic in 10th grade students of MIA MAN 2 Madiun are at a moderate level with a percentage of 77.3%. 3) there is a correlation between cognitive intelligence of students with their Arabic learning outcomes with results = 5%> 0.458710783 = 0.3002. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected